2018
DOI: 10.29020/nybg.ejpam.v11i1.2911
|View full text |Cite
|
Sign up to set email alerts
|

Convergence Rate of Implicit Iteration Process and a Data Dependence Result

Abstract: Abstract. The aim of this paper is to introduce an implicit S-iteration process and study its convergence in the framework of W-hyperbolic spaces. We show that the implicit S-iteration process has higher rate of convergence than implicit Mann type iteration and implicit Ishikawatype iteration processes. We present a numerical example to support the analytic result proved herein. Finally, we prove a data dependence result for a contractive type mapping using implicit S-iteration process.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…We also investigate the rate of convergence of the iteration process. Such considerations have appeared in the fixed point theory through works like [2,7,14,25].…”
Section: Introductionmentioning
confidence: 99%
“…We also investigate the rate of convergence of the iteration process. Such considerations have appeared in the fixed point theory through works like [2,7,14,25].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Yildirim and Abbas [12] have introduced the following implicit S-iteration procedure and showed that the convergence rate of this iteration is higher than the iterations (2) and (1).…”
Section: Introductionmentioning
confidence: 99%